Validity and Reliability of a 15 m Incremental Shuttle Run Test for Middle-aged Men - YOZA, Yoshiyasu; KUBO, Katsumi; MIKAWA, Kotaro; HASEO, Nobuhiro (Rigaku ryoho kagaku, 2020)
[Purpose] The aim of the present research was to investigate the validity and reliability of the 15 m Incremental Shuttle Run Test (15m ISRT), and to investigate the factors affecting 15m ISRT performance in middle-aged men. [Participants and Methods] Twelve middle-aged males performed three tests in a random order: the 15m ISRT, maximum traveling speed test, and lower leg muscle strength test. [Results] The correlation between 15m ISRT performance and VO2 was very high, r=0.95 (p<0.01). The only factor associated with 15m ISRT performance was peakVO2 (R2=0.88). Intraclass Correlation Coefficient (ICC) was very high for predicted peakVO2 calculated from the 15m ISRT performance vs. measured peakVO2. [Conclusion] Our findings indicate that the 15m ISRT is valid and reliable for evaluating peakVO2 of middle-aged adults.